Reconstrução e caracterização de estruturas anatómicas exteriores usando visão activa - Teresa Cristina de Sousa Azevedo (2005)
The work carried through had as main goals the familiarization and analysis of Computer Vision techniques for Three-Dimensional Reconstruction of Objects. From this work the development of a computer platform has been initiated.The present report has three chapters: in the first one, the goals are defined; in the second, the computer platform is presented, as well as some experimental results; in the third and last chapter, the conclusions relative to the study and work done are drawn and, finally, some perspectives of future work are given.